Direction of Trade Statistics Quarterly, December 2015. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper presents the quarterly issue of the IMF's Direction of Trade Statistics (DOTS). The term 'country,' as used in this publication, does not in all cases refer to a territorial entity that is a state as understood by international law and practice; the term also covers some non-sovereign territorial entities, for which statistical data are maintained and provided internationally on a separate and independent basis. The information on exports and imports by trading partners that countries report to the Fund varies in terms of frequency and currentness. No estimates, however, are compiled for periods prior to 1981 or based on benchmark data referring to 1980 or earlier. Moreover, data reported from countries' own records, even with longer delays, continually broaden the base of reported data, thereby replacing previously estimated figures. Area and world totals are compiled from reported data and these estimates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet